1988
DOI: 10.1111/j.1469-7610.1988.tb00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Intelligence and Special Abilities

Abstract: In summary, our research enables us to conclude that specific talents are found in people who differ widely in general intelligence levels and such talents should therefore be regarded as at least partly intelligence-independent. However, between normal and mentally handicapped populations and even within the idiot savant group, general cognitive capacity plays some part in determining the manner in which talents manifest themselves. Idiot savant special abilities can neither be regarded as the sole consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 14 publications
0
20
0
2
Order By: Relevance
“…The current study was conducted with an unselected group of children from normal classrooms, but the outcome of the research is highly consistent with prior research with children with special populations, including children who have been diagnosed with autism (Heaton & Wallace, 2004;O'Connor and Hermelin, 1987;O'Connor and Hermelin, 1988;Prewett et al, 1989;Selfe, 1983). In terms of autism in particular, there are several well-known case studies of children with severe cognitive deficits who exhibit superior drawing talent (O'Connor and Hermelin, 1987;Selfe, 1983).…”
Section: Discussionmentioning
confidence: 86%
“…The current study was conducted with an unselected group of children from normal classrooms, but the outcome of the research is highly consistent with prior research with children with special populations, including children who have been diagnosed with autism (Heaton & Wallace, 2004;O'Connor and Hermelin, 1987;O'Connor and Hermelin, 1988;Prewett et al, 1989;Selfe, 1983). In terms of autism in particular, there are several well-known case studies of children with severe cognitive deficits who exhibit superior drawing talent (O'Connor and Hermelin, 1987;Selfe, 1983).…”
Section: Discussionmentioning
confidence: 86%
“…O'Connor and Hermelin 26 found that calendrical calculators can use the rules and regularities in the calendar, and that those with special musical skills use the rules and structures that govern traditional tonal music, which helped them to remember music composed in accordance with these rules, but atonal music proved much more difficult to perform. Then, in the case of unexpected artistic skills, as has been stated, the child is able to extract the essential qualities of common objects in the visual world and memorise their essential features.…”
Section: Discussionmentioning
confidence: 99%
“…So all these children use strategies that are founded on the deduction and application of rules governing the material on which their special ability operates; and they may also generate new examples of such rule based structures. 26 It is interesting to speculate on the reasons for the loss and gain of artistic skills. Is it a question of the brain only being able to cope with a certain number of skills at one time?…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with ASD often display excellent memory in certain areas (e.g. cued-recall, factual information and rote-memory; Bennetto et al 1996;O'Connor and Hermelin 1988), whilst profound weaknesses exist in other domains (e.g. free-recall, source memory and temporal order memory; Bennetto et al 1996).…”
Section: Introductionmentioning
confidence: 99%